Superstrings in 2D backgrounds with R-R flux and new extremal black holes - Berkovits, N.; Gukov, S.; Vallilo, B. C. (Elsevier B.V., 2001)
The hybrid formalism is used to quantize the superstring compactified to two-dimensional target-space in a manifestly spacetime supersymmetric manner. A quantizable sigma model action is then constructed for the type II superstring in curved two-dimensional supergravity backgrounds which can include Ramond-Ramond flux. Such curved backgrounds include Calabi-Yau fourfold compactifications with Ramond-Ramond flux, and new extremal black hole solutions in two-dimensional dilaton supergravity theory. These black hole solutions are a natural generalization of the CGHS model and might be possible to describe using a supergroup version of the SL(2, R)/U(1) WZW model. We also study some dynamical aspects of the new black holes, such as formation and evaporation. (C) 2001 Published by Elsevier B.V. B.V.